Bistatic SAR System and Signal Processing Technology - Wang, Robert (Springer Singapore, 2018)
This book reports the latest results in the study of Bistatic/Multistatic SAR system and signal processing techniques. Novel research ideas and experimental verification have been collected on all kinds of configurations of Bistatic/Multistatic SAR system, including the preliminary construction of system model, imaging algorithm design, mission design and the corresponding application representations etc. Handy well-prepared tables are provided for readers' quick-reference, and the practical design of an interferometric SAR system is illustrated step by step. The book will be of interest to university researchers, R&D engineers and graduate students in Remote Sensing who wish to learn the core principles, methods, algorithms, and applications of Bistatic/Multistatic SAR system.